Chylous ascites following elective abdominal aortic aneurysm repair. Issue 12 (30th December 2020) - Bowden, Sylvie; Firdouse, Mohammed; Roche-Nagle, Graham
Abstract: Postoperative chylous ascites is a rare complication of abdominal surgery. Chyle depletion results in nutritional, immunologic and metabolic deficiencies, making it a serious and potentially life-threatening condition for which prompt diagnosis and management is imperative. A 72-year-old male was referred for open repair of a 62 cm juxtarenal abdominal aortic aneurysm (AAA). Following resumption of diet, he developed abdominal distention. Therapeutic paracenteses confirmed chylous ascites. Failed conservative management and lymphatic embolization lead to surgical sealance of lymphatic leak using glue. Postoperatively, a full diet was tolerated with no further ascites. Paracentesis is the diagnostic modality of choice in evaluating patients with ascites. Management is challenging and should be multifaceted and tailored to individual patient needs. Cornerstones of therapy include correction of the underlying etiology and conservative measures. When conservative measures fail, other interventions can be considered, such as somatostatin analogs, surgical ligation or glue embolization.